Video Surveillance of Today: Compressed Domain Object Detection, ONVIF Web Services Based System Component Communication and Standardized Data Storage and Export using VSAF – a Walkthrough - Sabirin, Houari; Bäse, Gero (IntechOpen, 2011)
None